An exploratory study in conceptualizing user view on digital taste using design thinking - Afdallyna Fathiyah Harun; Juhaida Ismail; Ho Yun Shiang; Nor Laila Md Noor; Hanif Baharin; Saiful Izwan Suliman (Institute of Advanced Engineering and Science, 2020)
Experiencing food involves accumulation of multiple senses, experienced through visuals, auditory and palatability. There has been significant growth in digitizing taste using electrical and thermal components to stimulate taste sensations where users need to lick devices or place a metal peripheral on their tongue. Such unnatural interaction appears undesirable motivating us to explore if taste experience could be stimulated by just viewing food visuals. This places considerable emphasis on understanding user association to food visuals and perceived food taste. Inability to understand their needs before-hand may result into a system with poor potentiality to trigger taste experience and not excite them to try the food they view on a digital platform. Using Design Thinking as an approach, we were able to identify user perceptions and expectations from food visuals as well as their desires on how images could trigger their interest to try the food. This paper presents the findings from the excursions and how this affected our strategy for the next phase of our research.